Avaliação em Larga Escala para a Educação Infantil: do Baby PISA ao Novo SAEB - Lima, Fernanda Hubner de (2023)
From the 1980s the State started to use evaluation as a mechanism of controlling and regulating public policies, especially the education, making the expression Evaluating State would have relevance and meaning in the field of administrative policies. In this sense, we understand large-scale evaluation as an action of the Evaluating State, which materializes in the Baby PISA and New SAEB evaluations. In Brazil, as of 2019, the New SAEB is aligned with the BNCC, including Early Childhood Education in the list of assessments in the national assessment system. In this way, we propose analyze the foundations and trends for large-scale assessment policy in Early Childhood Education, based on the guidelines of Baby PISA and the New SAEB. The research took a qualitative approach and was carried out through bibliographical, documentary and field research, in order to triangulate the data produced at international, national and local level, presenting a demonstration of how policies are manifesting trends and being implemented in practice. In this sense, we understand that large-scale evaluation disregards the peculiarities of Early Childhood Education, standardizing subjects according to neoliberal dictates and holding them responsible for the results obtained in the evaluations, in order to optimize the state's financial resources. Finally, considering the alignment with international policies, we observed the BNCC as an inducer of large-scale assessments for Early Childhood Education, which, in line with the domains assessed by Baby PISA, were incorporated into the list of national assessments through the New SAEB.